p53 and TFIIEα share a common binding site on the Tfb1/p62 subunit of TFIIH - Di Lello, Paola (National Academy of Sciences, 2008)
The general transcription factor IIH is recruited to the transcription preinitiation complex through an interaction between its p62/Tfb1 subunit and the α-subunit of the general transcription factor IIE (TFIIEα). We have determined that the acidic carboxyl terminus of TFIIEα (TFIIEα(336–439)) directly binds the amino-terminal PH domain of p62/Tfb1 with nanomolar affinity. NMR mapping and mutagenesis studies demonstrate that the TFIIEα binding site on p62/Tfb1 is identical to the binding site for the second transactivation domain of p53 (p53 TAD2). In addition, we demonstrate that TFIIEα(336–439) is capable of competing with p53 for a common binding site on p62/Tfb1 and that TFIIEα(336–439) and the diphosphorylated form (pS46/pT55) of p53 TAD2 have similar binding constants. NMR structural studies reveal that TFIIEα(336–439) contains a small domain (residues 395–433) folded in a novel ββααα topology. NMR mapping studies demonstrate that two unstructured regions (residues 377–393 and residues 433–439) located on either side of the folded domain appear to be required for TFIIEα(336–439) binding to p62/Tfb1 and that these two unstructured regions are held close to each other in three-dimensional space by the novel structured domain. We also demonstrate that, like p53, TFIIEα(336–439) can activate transcription in vivo. These results point to an important interplay between the general transcription factor TFIIEα and the tumor suppressor protein p53 in regulating transcriptional activation that may be modulated by the phosphorylation status of p53.